Листування Федора Павловича Матушевського з українськими письменниками у фондах київських архівів - Якобчук, С. (Літературознавчі обрії. Праці молодих учених, 2010)
The source study analysis of the correspondence of F P. Matushevsky with the famous Ukrainian writers is carried out in the article. Basic plots and themes of the letters are described. Significance and informative value of this correspondence for the study of cultural life and literary process in Ukraine during the XIX – the beginning of the XX century are determined by the author of the article.